SAT0084 Chest Pain is not Associated with Coronary Atherosclerosis in Patients with Rheumatoid Arthritis and Ankylosing Spondylitis. (23rd January 2014) - Rollefstad, S.; Olsen, I. C.; Hisdal, J.; Kvien, T. K.; Eirheim, A. S.; Pedersen, T. R.; Semb, A. G.
Abstract : Background: During cardiovascular (CV) risk stratification in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS), it can be difficult to distinguish between chest pain related to coronary atherosclerosis (CA), or to the rheumatic disease itself. Objectives: The aim was to evaluate associations between chest pain, CV risk factors and CA in RA and AS patients without established CV disease. Methods: Detailed information concerning chest pain and CV risk factors was obtained in 335 patients with RA and AS. In addition, 119 patients (RA n=86 and AS n=33) underwent multi detector computer tomography (MDCT) coronary angiography. 1 Results: Thirty-one percent (104/335) reported chest pain. Only 6 patients (1.8%) had atypical angina pectoris (pricking pain at rest). In 50 patients with chest pain, 26 (52.0%) had CA, while in 69 patients without chest pain, 51 (73.9%) did have CA. In a logistic regression analysis with CA (by MDCT coronary angiography) as the dependent variable, chest pain was not associated with CA (p=0.28). About 30 % of CA was explained by any of the three following CV risk calculators: SCORE (systemic coronary risk evaluation), Framingham and Reynolds in these models (Table 1 ). Image/graph: Conclusions: Chest pain was surprisingly infrequently reported considering the underlying rheumatic joint disease, but when present, chest pain was of limited value in CV risk evaluation. References: Hoffmann MH, Shi H, Schmitz BL, Schmid FT, Lieberknecht M, Schulze R et al. Noninvasive coronary angiography with multislice computed tomography. JAMA 2005; 293(20):2471-2478. Disclosure of Interest: None Declared